Strategies for Fostering HPV Vaccine Acceptance (Hindawi Limited, 2006)
Vaccines that protect against infection with the types of human papillomavirus (HPV) commonly associated with cervical cancer (HPV 16 and 18) and genital warts (HPV 6 and 11) are expected to become available in the near future. Because HPV vaccines are prophylactic, they must be administered prior to exposure to the virus, ideally during preadolescence or adolescence. The young age of the target vaccination population means that physicians, parents, and patients will all be involved in the decision-making process. Research has shown that parents and patients are more likely to accept a vaccine if it is efficacious, safe, reasonably priced, and recommended by a physician. Widespread education of physicians, patients, and parents about the risks and consequences of HPV infection and the benefits of vaccination will be instrumental for fostering vaccine acceptance.